Report on the live birth rates and neonatal outcomes of ART patients at Aevitas Fertility Clinic : implications of a Frozen Embryo Transfer (FET) program - Meiring, Elizabeth (Stellenbosch : Stellenbosch University, 2020)
Thesis (MNutr)--Stellenbosch University, 2020.